Penyelesaian Sengketa Konflik Kepemilikan Tanah dengan Pendekatan Litigasi di Pengadilan Tata Usaha Negara - Anggita Anggita (Savana, 2024)
Land is an important thing in human life. In Indonesia, land is regulated in basic or basic rules, namely the Basic Agrarian Law (UUPA) of 1960. To guarantee ownership rights to land owned by someone, evidence is needed to support this ownership, namely by registering land and certifying it. land. However, of course these things cannot be separated from the existence of land disputes which can arise for various reasons. The aim of this research is to find out the regulations regarding land registration and the purpose of land registration as well as the benefits of land certificates and how to analyze examples of land disputes. . The method used in this article is a juridical-normative approach and uses descriptive-analytical research. The results of the research are that dispute resolution can be carried out by the National Land Agency or through litigation, namely through the State Administrative Court (PTUN). An example of a land dispute resolution submitted through the PTUN is Decree Number: 3/G/2023/PTUN.YK. Land certificate disputes that occur can be resolved through the Administrative Court, guided by applicable regulations. The results obtained after analyzing the case that occurred, in the end the lawsuit that was filed could not be followed up due to administrative and/or legal defects.